A role for AID in chromosome translocations between c-myc and the IgH variable region - Dorsett, Yair (The Rockefeller University Press, 2007)
Chromosome translocations between oncogenes and the region spanning the immunoglobulin (Ig) heavy chain (IgH) variable (V), diversity (D), and joining (J) gene segments (Ig V-J(H) region) are found in several mature B cell lymphomas in humans and mice. The breakpoints are frequently adjacent to the recombination signal sequences targeted by recombination activating genes 1 and 2 during antigen receptor assembly in pre–B cells, suggesting that these translocations might be the result of aberrant V(D)J recombination. However, in mature B cells undergoing activation-induced cytidine deaminase (AID)-dependent somatic hypermutation (SHM), duplications or deletions that would necessitate a double-strand break make up 6% of all the Ig V-J(H) region–associated somatic mutations. Furthermore, DNA breaks can be detected at this locus in B cells undergoing SHM. To determine whether SHM might induce c-myc to Ig V-J(H) translocations, we searched for such events in both interleukin (IL) 6 transgenic (IL-6 tg) and AID(−/−) IL-6 tg mice. Here, we report that AID is required for c-myc to Ig V-J(H) translocations induced by IL-6.